The impact of smoke-free policies on smoking at outdoor sports clubs: a qualitative study. (January 2023) - Smit, R.A.; Garritsen, H.H.; Kunst, A.E.; Rozema, A.D.
Abstract: Objectives: Smoking may still occur at sports clubs with an outdoor smoke-free policy (SFP). This study aims to map the occurrence of smoking at various sports clubs in the Netherlands and to understand why smoking occurs at some clubs but not at others. Study design: This was a qualitative design in the form of semistructured interviews. Methods: Semistructured interviews (n = 34) were held online with smoking and non-smoking members of 17 Dutch outdoor sports clubs (in field hockey, korfball, football, and tennis) with an outdoor SFP. Data were analyzed using content analysis. Results: We identified four situations where smoking still occurred: (1) directly at the entrance, (2) at some distance from the entrance, (3) in particular places on the premises, and (4) in various places or on occasions when alcohol is consumed. Smoking directly at the entrance was most often perceived as a bothersome situation that was difficult to avoid. The occurrence of these situations differed per sports club depending on the scope of the SFP (the comprehensiveness of the SFP and the presence or absence of a smoking area) and factors influencing policy compliance (physical characteristics of the sports club's premises, the presence or absence of children, and several enforcement difficulties). Conclusion: In some sports clubs, smoking remained common on the premises despite an outdoor SFP. Exposure to second-hand smoke might be reduced by formulating a comprehensive SFP, improving policy compliance also in situations where children are absent, and organizing the enforcement of the policy.